PERAN PENDIDIK DALAM MEMBENTUK GENERASI MUDA SEBAGAI AGEN PERUBAHAN SOSIAL DI ERA MODERN - Syifa Fauziah Ahmad; Putri Gita Lestari; Ananda Dwi Putri (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study examines the role of educators as agents of social change in shaping the younger generation in the era of globalization and modernity. The aim is to analyze the contribution of educators in strengthening character, social awareness, and 21st century skills in students. The method used is library research by relying on available sources, such as literature, articles, books, and relevant secondary data. The results of the study show that teachers play a central role as educators, mentors, and moral role models, but face challenges such as demands for digital literacy, changes in student character, and administrative burdens. The strategies implemented include active learning, increasing digital competence, and strengthening character education. In conclusion, the strategic role of educators requires support from educational policies and innovations so that the younger generation is ready to become agents of social change in society.